2016
DOI: 10.1111/apm.12634
|View full text |Cite
|
Sign up to set email alerts
|

Primary giant cell tumor of the female breast: a diagnostic red herring with therapeutic implications

Abstract: Primary giant cell tumor of the female breast is extremely rare. Major diagnostic difficulty is encountered not only by the surgeon but also by the radiologist and pathologist. Pathologically, it is similar to the bone and soft tissue counterparts. However, this is not always true. We describe a patient presenting clinically as cystosarcoma phyllodes and histopathological examination revealed a primary giant cell tumor which was confirmed by immunohistochemistry and electron microscopy. Interestingly, an intim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Clinically the majority of these patients have presented with large masses, with the current case being the second to be clinically assessed as a phyllodes tumour. 6 One reported case was associated with an intraductal papilloma 7 and another had an adjacent separate tumour, histologically in keeping with ductal carcinoma in situ . 9 On imaging, the majority of the cases reported well circumscribed tumours on mammogram, and all had hypoechoic cystic regions with solid tumour on ultrasound.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Clinically the majority of these patients have presented with large masses, with the current case being the second to be clinically assessed as a phyllodes tumour. 6 One reported case was associated with an intraductal papilloma 7 and another had an adjacent separate tumour, histologically in keeping with ductal carcinoma in situ . 9 On imaging, the majority of the cases reported well circumscribed tumours on mammogram, and all had hypoechoic cystic regions with solid tumour on ultrasound.…”
Section: Discussionmentioning
confidence: 93%
“…Osteoclast-like giant cell tumour of the soft tissues of the breast is a rarely diagnosed primary tumour of the breast with only eight cases previously reported in the literature. 1 , 2 , 4 , 5 , 6 , 7 , 8 , 9 The prognosis is therefore still unknown. Although it is usually considered a benign tumour, it may recur locally but seldom metastasizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor sizes ranged from 2.5 to 13 cm (the median size was 3 cm). The physical examinations or image examinations showed well-circumscribed masses in 7 cases (17)(18)(19)(20)(21) and irregular-shaped masses in 2 cases (22,23). Of the 8 cases with follow-up results, 1 patient died of lung metastasis after the initial presentation, and in the other 7 patients, local recurrence or distant metastasis did not occur (18).…”
Section: Discussionmentioning
confidence: 98%
“…Primary giant cell tumors in the breast are not common. Nine studies had reported primary giant cell tumors of soft tissue (GCT-ST) arising in the breast (15)(16)(17)(18)(19)(20)(21)(22)(23). One case occurred in an elderly male, and the other 8 cases occurred in females.…”
Section: Discussionmentioning
confidence: 99%